The Effects of Cayenne Pepper Juice (Capsicum frutescens L.) on Decreasing the Number of Goblet Cells in the Small Intestine Mucosa of Rats - Usman, Sherly; Makiyah, Sri Nabawiyati Nurul; Danantika, Wiriasti (Fakultas Kedokteran Universitas Lambung Mangkurat, 2024)
Cayenne pepper contains capsaicin and irritates the mucous of the digestive tract. Goblet cells play a role in mucosal defense because they produce mucin. In previous research, cayenne pepper juice caused gastric mucosal damage and improve at certain doses. This Research is a continuation of previous research, which was to determine the effect of cayenne pepper on the number of goblet cells of the small intestine mucosa of rats and is additional material for the development of therapy for digestive disorders. An experimental study with a post-test only and control group design, used 20 male rats, divided into 1 control (K) and 4 treatment groups (C45, C90, D135, and E180). Cayenne pepper juice was given according to the dose of the group using a gastric probe for 6 days. On the 7th day, the small intestine was taken and processed on histological preparation. Microscopic observations of goblet cells counted on average every 100 epithelia in 20 villi in 15 fields of view and the mean number was tested by One Way ANOVA and Post Hoc test. Analysis showed a significantly different mean number of goblet cells between groups (p<0.05), the highest was in the C135 (34.100 ± 1.274), the lowest mean was in the K (12.050 ± 0.462), and there was a decrease in the mean number in the C180 (28.525 ± 2.309). Cayenne pepper juice had effected the highest increase in the number of goblet cells at a dose of 135 mg and decreased at the dose of 180 mg of cayenne pepper in the small intestine of rats.